A fuzzy logic urea dosage controller design for two-cell selective catalytic reduction systems. (July 2018) - You, Kun; Wei, Lijiang; Jiang, Kai
Abstract: Diesel engines have dominated in the heavy-duty vehicular and marine power source. However, the induced air pollution is a big problem. As people's awareness of environmental protection increasing, the emission regulations of diesel-engine are becoming more stringent. In order to achieve the emission regulations, the after-treatment system is a necessary choice. Specifically, the selective catalytic reduction (SCR) system has been widely applied to reduce the NOX emissions of diesel engine. Different from single-cell SCR systems, the two-cell systems have various benefits from the modeling and control perspective. In this paper, the urea dosage controller design for two-cell SCR systems was investigated. Firstly, the two-cell SCR modeling was introduced. Based on the developed model, the design procedure for the fuzzy logic urea dosage controller was well addressed. Secondly, simulations and comparisons were employed via an experimental verification of the whole vehicle simulator. And the results showed that the designed controller simultaneously achieved high NOX reduction rate and low tail-pipe ammonia slip. Highlights: The two-cell SCR modeling is introduced. The design procedure for fuzzy logic urea dosage controller is addressed. The control performance of the designed fuzzy logic controller is evaluated. Comparisons are conducted between fuzzy logic controller and PID controller.